De epigrammate Coo aetatis classicae - Hallof, Klaus (Hyperboreus, 2015)
A newly found fragment may be added to a Coan funerary inscription (no. 20 Paton – Hicks). The inscription consists of two elegiac distiches and dates from the Classical period.